Indonesian online news and digital culture: a media ecology perspective - Bruce Dame Laoera; Tangguh Okta Wibowo (Faculty of Communications Science, Dr. Soetomo University, 2023)
The number of Internet users in Indonesia continues to increase, with more and more people using electronic gadgets connected to the Internet. It is also quite clear to see the phenomenon related to the emergence of online news in the digital realm. The researchers review and characterise Indonesian online news from the media ecology perspective. By doing library research, a literature review will be composed and used to describe online news and digital culture in Indonesia in media ecology. The result shows that the increasing use of the Internet has resulted in the rise of online news media, which seem to have replaced traditional media. In the context of Indonesia's digital culture, multimedia features in online news have the potential to attract readers' interest. At the same time, social media provides space for independent online news and community participation in the digital world to shape social, political, and cultural values.